In Silico Analysis of Variants of Uncertain Significance in AP4S1 Gene - Chaudry, Sobia Nazir; Akhtar, Ammara; Naeem, Ayman; Husaain, Dr. Mureed (BioScientific Review, 2020)
Hereditary spastic paraplegia is a group of heterogeneous neurological disorders with genetic etiologies. It is characterized by spasticity in lower limbs along with neurological complications. Sequencing technologies have identified numerous disease causing variants in AP4S1 gene. However, many very low frequency variations in AP4S1 have the potential to cause hereditary spastic paraplegia in a recessive inheritance manner. This study was designed to identify these potential disease causing variants in AP4S1 gene using in silico tools. These tools predict the effects of deleterious variants on protein function and pre-mRNA splicing. To predict the pathogenicity of missense variants PhD-SNPg, PROVEAN, SNPs&GO, and CADD were used. Splice site variants were analyzed using Spliceman, SPiCE, and Human Splice Finder (HSF). In silico analysis identified six missense and five splice site variants with the potential to cause hereditary spastic paraplegia. Copyright(c) The Author